System podatkowy a funkcjonowanie małych i średnich przedsiębiorstw - Kozielec, Jadwiga (My University, 2015)
W pracy omówiono formy opodatkowania. Przedstawiono zróżnicowane formy rozliczeń obowiązujące w naszym kraju. Praca zawiera ankietę przeprowadzoną w Nowym Targu na próbie 20 przedsiębiorców. W oparciu o przeprowadzone analizy można wywnioskować że mieszkańcy Nowego Targu generalnie nie są zadowoleni z systemu podatkowego oraz barier na jakie napotykają rozpoczynając i prowadzących działalność gospodarczą.

The following master thesis presents an issue of taxation forms. It shows diversity of alternative forms of taxation valid in Poland of wich you can choose from. The analysys is based on a survey of twenty entrepreneurs conducted in Nowy Targ. Based on the studies it can be concluded that the residents of Nowy Targ are dissatisfied with the tax system and barriers witch they have to face to start up and run business.
The tax system and the functioning of small and medium-sized enterprises
Keywords: formy opodatkowania; podatek; przedsiębiorstwo; system podatkowy; podmiot gospodarczy; podatnik; tax; business; tax system; trader; tax payer; taxation forms